Performance support team effectiveness in elite sport: a narrative review - Stewart, P.; Fletcher, D.; Arnold, R.; McEwan, D. (International Review of Sport and Exercise Psychology, 2026)
In pursuit of competitive advantage, elite sport organizations are increasingly relying on the support of diverse sport medicine and sport science staff, who are collectively referred to as the performance support team. Whilst it has been suggested that the accumulative input from diverse multiteam systems has the potential to contribute to a resultant whole that is greater than the sum of its parts, team effectiveness is reliant on more than the mere aggregate of diverse experts. The aim of this narrative review was to appraise, summarize, and apply pertinent performance support team literature to a conceptual framework for teamwork and team effectiveness in sport. It specifically explores team effectiveness, with reference to its inputs (i.e. characteristics of individual, team, and environment) and mediators (i.e. team processes and emergent states). This review provides an insight into the individual (i.e. disciplinary knowledge, technical competency, and interpersonal qualities), team (i.e. team composition and leadership), and external (i.e. hierarchical arrangement and environmental factors) inputs that are necessary for team effectiveness, as well as the mediators (i.e. behavioral processes and emergent states) that translate such inputs into desired outcomes.